2012
DOI: 10.1016/j.bbabio.2011.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Damage to mitochondrial complex I during cardiac ischemia reperfusion injury is reduced indirectly by anti-anginal drug ranolazine

Abstract: Ranolazine (Ran), an anti-anginal drug, is a late Na+ channel current blocker that is also believed to attenuate fatty acid oxidation and mitochondrial respiratory complex I activity, especially during ischemia. In this study, we investigated if Ran's protective effect against cardiac ischemia/reperfusion (IR) injury is mediated at the mitochondrial level and specifically if respiratory complex I (NADH oxidoreductase) function is protected. We treated isolated and perfused guinea pig hearts with Ran just befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 68 publications
5
61
1
Order By: Relevance
“…Therapeutic effects of ranolazine occur via two mechanisms: (1) inhibition of late inward sodium current and, hence, prevention of Ca 21 overload in ischemic hearts; and (2) inhibition of fatty acid oxidation and shift of metabolism toward glucose oxidation (52). Therefore, ranolazine may preserve mitochondrial supercomplexes, in part by restoring cardiolipin and, hence, electron flux in mitochondrial Fe-S clusters (53). Ranolazine also has been shown to indirectly stabilize SERCA in hearts of dogs with mild cardiac failure (18).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic effects of ranolazine occur via two mechanisms: (1) inhibition of late inward sodium current and, hence, prevention of Ca 21 overload in ischemic hearts; and (2) inhibition of fatty acid oxidation and shift of metabolism toward glucose oxidation (52). Therefore, ranolazine may preserve mitochondrial supercomplexes, in part by restoring cardiolipin and, hence, electron flux in mitochondrial Fe-S clusters (53). Ranolazine also has been shown to indirectly stabilize SERCA in hearts of dogs with mild cardiac failure (18).…”
Section: Discussionmentioning
confidence: 99%
“…27 It has been demonstrated that, after ischemia, ranolazine improves mitochondrial function and that ranolazine is also protective of mitochondria in ischemia reperfusion injury. [37][38][39] In a previous study, we have demonstrated that improvement of mitochondrial function is cardioprotective. 40 This may support the notion that ranolazine improves mitochondrial function after LDVF.…”
Section: Dynamics After Ldvfmentioning
confidence: 98%
“…Our methods have been described in detail previously (1,12,(21)(22)(23). Unless otherwise indicated, all drugs were purchased from Sigma (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…The membrane was then stripped using stripping buffer (100 mM 2-mercaptoethanol, 2% SDS, 62.5 mM Tris·HCl pH 6.7) at 50°C, followed by three washes in TBSt. Equivalence of protein loading was confirmed with an antibody against cytochrome c oxidase (complex IV) subunit 1 (Invitrogen) since complex IV is relatively more resistant to IR injury than complex I (12). Densitometry was performed with Image J software.…”
Section: Animals All Investigations Conformed To the Guide For The Cmentioning
confidence: 99%